Use of a Disposable Real-Time CT Stereotactic Navigator Device for Minimally Invasive Dog Brain Biopsy through a Mini-Burr Hole - Flegel, Thomas; Podell, Michael; March, Philip A.; Chakeres, Donald W. (American Journal of Neuroradiology, 2002)
Summary: We assessed the feasibility, accuracy, and safety of securing site-selective brain biopsy specimens by using a real-time CT-guided stereotactic navigation system through a mini-burr hole in the skulls of two dogs. Two beagle dogs each underwent two biopsy procedures. Our results indicated that the navigation system was accurate, safe, fast, and reliable for performing real-time brain biopsy in dogs and eliminated the need or risk of a standard-flap craniotomy.